Perancangan Aplikasi Media Pembelajaran Seni Tari bagi Siswa Tunarungu berbasis Android - Sri Wahyuni; M. Fadhil Muhaimin; A. Muhammad Syafar (Prosiding SISFOTEK, 2023)
In its implementation, teaching dance for deaf students at SLB-B YPPLB Makassar, still has obstacles, namely a complicated control process and teaching dance consistency which still uses conventional methods, namely hand clapping. So, in this research, the author makes an application as a forum for learning dance that will be used by students where there is dance introduction material, learning dance consistency exercises through visual media, and receiving feedback from the teacher. Based on questionnaires that have been filled out by students, it can be concluded that the application made is in accordance with the dance learning method and makes it easier for them in the process of learning dance tempo.